Cultural Humility, Human Research Ethics Review, and Informed Consent. (April 2023) - Lahman, Maria K. E.; Landram, Suzanne; Teman, Eric D.; Kincaid, Tyler
The United States, through research ethics review, is complicit in ethically recolonizing countries into U.S. dominant understandings. This review and consent are seen as an all-encompassing ethical understanding and a discrete, one-time experience. Drawing on personal experiences and in-depth interviews with international and domestic subculture research participants and researchers, the authors argue that the United States ethics review must move toward a nuanced understanding of human ethics review that exhibits cultural responsiveness within culturally complex research, with a focus on cultural humility. Power, gender, sexuality, and relationships between participants, researchers, and research ethics boards are discussed.